A Review of Newly Diagnosed Glioblastoma - Bryan Oronsky; Tony R. Reid; Arnold Oronsky; Navjot Sandhu; Susan J. Knox (Frontiers in Oncology, 2021)
Glioblastoma is an aggressive and inevitably recurrent primary intra-axial brain tumor with a dismal prognosis. The current mainstay of treatment involves maximally safe surgical resection followed by radiotherapy over a 6-week period with concomitant temozolomide chemotherapy followed by temozolomide maintenance. This review provides a summary of the epidemiological, clinical, histologic and genetic characteristics of newly diagnosed disease as well as the current standard of care and potential future therapeutic prospects.